A-V Fistula Blood Flow and Complications: A One Year Survey (Journal of Medicine, 2014)
Background: Worldwide haemodialysis(HD) is the mostly used method of renal replacement therapy. Arteriovenous fistula use is on rise due to Fistula First Initiative due to least complications of fistulae than catheters.But they are also subjected to many complications. Thereby appropriate surveillance of the fistulae is important.Objectives: To measure the blood flow as well as fistula related complications in study population. Materials and Methods: This was a cross sectional study, conducted in the department of Nephrology, Dhaka Medical College Hospital during September 2010 to December 2011.Total 118 subjects were included in the study. Besides visualization technique colour Doppler ultrasonogram of fistula and  echocardiography were performed for each patients. Results: Most of the patients had adequate fistula flow. Aneurysm was most common complication. Many subjects were suffered from primary and secondary fistula failure. Conclusion: Arterio-Venous fistula is subjected to many complications and appropriate surveillance should be launched to detect complications and to prevent fistula failure.DOI: http://dx.doi.org/10.3329/jom.v15i2.20681 J MEDICINE 2014; 15 : 110-113